Language learning motivation as ideological becoming. (April 2017) - Harvey, Lou
Abstract: This article offers a new reading of motivation based on the dialogical theory of Mikhail Bakhtin. I join Hennig (2013) and Clarke and Hennig (2013) in calling for approaches to language learning motivation which take account of the ways in which language learning is meaningful to learners' lives. While Clarke and Hennig's analysis of motivation as a Foucauldian process of ethical self-formation answers this call, it does not theorise the relationship between language learning motivation and general motivation for learning. My analysis offers a theorisation of language which creates this conceptual bridge. Drawing on Bakhtin, I present an account of language learning motivation with theorises language and learning, positing language learning motivation as a holistic process of ideological becoming, inextricably bound to learners' wider life-learning. I illustrate this framework through the story of Dmitry, a Russian learner of English as a second language, demonstrating how his engagement with the language and its speakers contributed to his motivation for learning the language and for a wider process of learning to be in the world. I conclude by positing that by conceptualising the connections between language, learning and motivation, ideological becoming synthesises and theoretically enriches extant psychological approaches to language learning motivation.